Rancang Bangun Aplikasi Sistem Informasi Jasa Service Sepeda Motor Berbasis Android - Arie Oktavianto; Khozainuz Zuhri; Yodhi Yuniarthe; Romi Hendri (Jurnal Teknologi dan Informatika (JEDA), 2022)
With the increase of smartphone users and motor users, it can be designed a service provider application that is devoted to motorcyclists. With the large number of motor vehicles, there are also many service services or maintenance services and motor vehicle repairs to help motorists in getting comfortable motor vehicles by doing regular motor vehicle maintenance. Manual recording is very difficult for the workshop when it comes to providing information to customers about service schedules. In addition to difficulties from the workshop side, difficulties are experienced by the customer where in the intended workshop. The quota provided by the party has sometimes exceeded the maximum limit provided and customers must find another workshop or have to reschedule the next day.